Sperm morphometry and chromatin condensation in Nelore bulls of different ages and their effects on IVF - Kipper, B. H. [UNESP]; Trevizan, J. T. [UNESP]; Carreira, J. T.; Carvalho, I. R. [UNESP]; Mingoti, G. Z. [UNESP]; Beletti, M. E.; Perri, S. H.V. [UNESP]; Franciscato, D. A. [UNESP]; Pierucci, J. C. [UNESP]; Koivisto, M. B. [UNESP] (Elsevier, 2017)
The aim of this study was to evaluate the chromatin packing and sperm head morphometry of cryopreserved semen of Nelore bulls (Bos taurus indicus) of different ages. Furthermore, the influence of the degree of chromatin compaction on in vitro embryo production (IVP) was investigated. Forty bulls were divided into three groups: young (1.8–2 years), adult (3.5–7 years), and senile (8–14.3 years). The ejaculates were frozen according to standards established by the Artificial Insemination Center located in the Southeast of Brazil. Toluidine blue staining was used for simultaneous evaluation of the sperm chromatin and sperm head morphometry. Chromomycin A3 (CMA3) was applied to analyze sperm protamination and IVP for embryonic development. Spermatozoa of young bulls presented higher values for area (A, pixels), perimeter (P, pixels), and width (W, pixels) compared to adults and senile (young: A = 1848.5 ± 119.79, P = 10.23 ± 0.29, and W = 1.95 ± 0.1; adults: A = 1672.9 ± 104.46, P = 9.86 ± 0.33, and W = 1.81 ± 0.06; senile: A = 1723.1 ± 124.41, P = 9.97 ± 0.33, and W = 1.83 ± 0.09; P < 0.0001) and showed higher protamination deficiency when analyzed by CMA3 (young: 1.57 ± 0.76; adults: 1.09 ± 0.63, and senile: 0.90 ± 0.59; P < 0.05). Likewise, variables of sperm head size (A, P, and W) and protamination assessed by CMA3 showed negative correlation with age and positive correlation with ellipticity, evaluated by toluidine blue method (P < 0.05). Sperm head area was larger in spermatozoa presenting chromatin instabilities than spermatozoa without chromatin alteration (P < 0.0001). There was no difference in IVP when using semen with larger or smaller portions of spermatozoa with chromatin instabilities, indicating that the proportion of sperm with abnormal chromatin compaction (4%–16.15%) did not interfere with early embryonic development. From our results, it can be concluded that sperm of young Nelore bulls have larger heads compared to adults and senile due to reduced protamine content when evaluated by CMA3 and higher proportion of major sperm defects assessed by differential interference contrast microscopy.
Keywords: Bovine; Chromomycin A3; Fertility; Semen; Toluidine blue